Membangun Spirit Kebangsaan Kaum Muda di Tengah Fenomena Radikalisme - Endang Supriadi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
AbstrakThe opening of the texts of political freedom and democratization following the fall of the New Order regime not only provided space for the emergence of various expressions built on primordial sentiments and identities but also paved the way for the expansion of radicalism. Reports by a number of survey institutions indicate that Indonesia is still a fertile ground for the production and reproduction of radical ideologies that allow the continued expansion of the radical organization or network. This threat is exacerbated by high public support for intolerance and violence.This article explores how the spirit of nationality for young people in the midst of the emergence of intolerant attitudes in society, the attitude of monopolizing the truth in religion that led to acts of terror in society. It needs dialogue and reconciliation honestly and openly. The deradicalization program must now be strengthened with elements of society to create a safe and peaceful atmosphere. As a consequence of choice as a democratic country, the principle of proportionality is very important to be put forward, so that there is no majority domination and minority tyranny.Keywords: nationality, young people, radicalism, deradicalism